APLIKASI PUPUK ORGANIK CAIR DAN BIOPESTISIDA PADA PERTANIAN PADI ORGANIK DI SUBAK REJASA KECAMATAN PENEBEL KABUPATEN TABANAN - N.N. Soniari; N.M. Witariadi; N.K. Karyati (Buletin Udayana Mengabdi, 2018)
One of the goals of science and technology for the Region of Jegu and RejasaVilages in Penebel District,Tabanan Regency is a healthy increase rice productivity by application of liquid organic fertilizer andartificial biopesticides farmers themselves. The method adopted to achieve these goals is through education,training, simulation science and technology, mentoring, and design appropriate technology applied.All suchactivities are realized in the form of a field school that was attended by 25 members of SubakRejasa bymaking healthy rice demonstration plot 25 acres.POC and biopesticide made from animal waste, sugar cane,Gamal, yam tubers and other local materials, applied at a dose of 450 ml / 25 L of water every week. Liquidorganic fertilizer and biopesticide made by members of SubakRejasa have done laboratory analysis with thefollowing results: the content of C-org (1,540%): N (0.160%); P (85.120 ppm); K (95.400 ppm); pH (7.78)and DHL (32,200 mS). The results of the application of POC and biopesticideson the rice varieties "Inpari30", quite good, vegetative growth performance lush, green leaves, stronger stems no pests anddiseases,number of tillers 20 -24, .and the generative phase, pithy grain, grain number between 185-255 /stalkand grain yield at harvest 5.8 tonnes / ha. The processing of livestock wastes into POC and biopesticides provides a new source of additional income for farmers in addition to economic efficiency in the use offertilizers and the slow return of biodiversity.